1989
DOI: 10.1002/mrd.1120240109
|View full text |Cite
|
Sign up to set email alerts
|

Acrosomal function of human spermatozoa with normal and abnormal head morphology

Abstract: In previous studies we have shown differences in the function of morphologically normal and abnormal sperm by evaluating their flagellar movements and swimming trajectories. In this study we have compared the capability of morphologically normal and abnormal human sperm to undergo an acrosome reaction after incubation with human follicular fluid. Semen samples were studied from 6 research donors and 21 semen evaluation patients. All men had normal semen by clinical criteria. Semen was prepared either by a two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In our cohort, the increase in the proportion of sperm with specific head shapes had an influential effect on the rates of AR, with the rate being positively correlated to those sperm with normal (oval) heads. These findings are in agreement with the results of Fukuda et al (1989), who reported that morphologically abnormal sperm had lower rates of acrosomal loss after incubation with FF than normal sperm.…”
Section: Discussionsupporting
confidence: 93%
“…In our cohort, the increase in the proportion of sperm with specific head shapes had an influential effect on the rates of AR, with the rate being positively correlated to those sperm with normal (oval) heads. These findings are in agreement with the results of Fukuda et al (1989), who reported that morphologically abnormal sperm had lower rates of acrosomal loss after incubation with FF than normal sperm.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the decline in acrosomal integrity following dilution of the cryoprotectant and centrifugation, it appeared that cheetah spermatozoa were susceptible to both osmotic damage and centrifugal forces. It has been previously reported that the proportion of structurally normal spermatozoa in a raw ejaculate may be directly related to overall sperm function due to a negative association between abnormal sperm morphology and acrosomal function [6]. Indeed, there was a strong positive correlation between the percentage of normal spermatozoa and the proportion of these cells with intact acrosomal membranes in raw ejaculates.…”
Section: Discussionmentioning
confidence: 93%
“…In endothelial or alveolar type II cells, molecules such as the von-Willebrand factor (50–20000 kDa) and the surfactant are densely packed in cigar shaped Weibel-Palade bodies (0.5 × 1.5 μm) and lamellar bodies respectively (diameter 1.5–2 μm). Finally, a peculiar case is sperm where a complex mixture of proteins needed for fertilization such as hyaluronidase and acrosin, are released from the acrosome, a large single cup shaped organelle that can reach a few microns in size [67]. …”
Section: Regulated Exocytosismentioning
confidence: 99%